PENERAPAN MODEL PEMBELAJARAN STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD - Mutiara Aulia Marzi; Widayati Widayati (Universitas Ahmad Dahlan, 2019)
This study aims to improve mathematics learning outcome of fifth grade students by using STAD learning model at SD Muhammadiyah Domban 1 Sleman. This type of research was classroom action research. Data collection techniques used tests and observations. The data obtained in this study were then analyzed by using quantitative and qualitative descriptive analysis. This study shows that the use of STAD learning model can improve mathematics learning outcome among the fifth grade students of SD Muhammadiyah Domban. The learning outcome obtained from the cycle I were still not optimal in which there were only 67.7% of students who meet the minimal standar score then proceed to cycle II. In cycle II, the application of STAD learning model runs well, it can be seen from the students learning outcome of the cycle I in which there were 87.1 % of students who had reached the minimal standard score)